PENGARUH LITERASI EKONOMI DAN PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BERWIRAUSAHA - Altri Wahida; Madrianah Madrianah (AkMen JURNAL ILMIAH, 2023)
The purpose of this study was to find out how economic literacy and the use of Instagram social media affect people's interest in starting their own business. This research was conducted using quantitative methods and as many as 60 students from the city of Palopo participated in this study. The results of the study show that economic literacy has no effect on the interest in entrepreneurship, while the use of Instagram social media has a significant effect. In addition, the use of Instagram social media has a significant influence on one's business interests in Palopo City.